Diseño arquitectónico del centro Integral de atención al migrante en Bucaramanga, Santander “en busca de lo perdido” (2023)
Colombia is the main receiving country for the majority of Venezuelan migrants, with Santander being the sixth region with the largest population settled in its territory. They come on foot from Cúcuta to Bucaramanga, where they have been gradually staying, leading the city to overcrowd, which is why it suffers a great problem of invasion of public space (Ocampo, 2015)